2017
DOI: 10.1002/2017gl072975
|View full text |Cite
|
Sign up to set email alerts
|

Air‐Sea exchange of biogenic volatile organic compounds and the impact on aerosol particle size distributions

Abstract: We report simultaneous, underway eddy covariance measurements of the vertical flux of isoprene, total monoterpenes, and dimethyl sulfide (DMS) over the Northern Atlantic Ocean during fall. Mean isoprene and monoterpene sea‐to‐air vertical fluxes were significantly lower than mean DMS fluxes. While rare, intense monoterpene sea‐to‐air fluxes were observed, coincident with elevated monoterpene mixing ratios. A statistically significant correlation between isoprene vertical flux and short wave radiation was not o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
95
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 63 publications
(112 citation statements)
references
References 79 publications
(121 reference statements)
15
95
2
Order By: Relevance
“…HiWinGS meteorological data, sea state, eddy correlation flux measurements, and gas transfer coefficients for CO 2 and DMS will be presented in this section. We show summary plots of supporting measurements as necessary, but for additional detail the reader is directed to other HiWinGS publications: Yang et al () have previously reported measurements and model results for methanol and acetone fluxes, sensible heat flux, and wind stress; Kim et al () present results for air‐sea emissions of biogenic organic compounds and their influence on aerosol size distributions; and Brumer et al () report on the wind and sea state dependencies of whitecap fraction. Additional papers detailing empirical gas transfer parameterizations, 2‐D wave statistics and bubble methods and measurements are in preparation.…”
Section: Resultsmentioning
confidence: 99%
“…HiWinGS meteorological data, sea state, eddy correlation flux measurements, and gas transfer coefficients for CO 2 and DMS will be presented in this section. We show summary plots of supporting measurements as necessary, but for additional detail the reader is directed to other HiWinGS publications: Yang et al () have previously reported measurements and model results for methanol and acetone fluxes, sensible heat flux, and wind stress; Kim et al () present results for air‐sea emissions of biogenic organic compounds and their influence on aerosol size distributions; and Brumer et al () report on the wind and sea state dependencies of whitecap fraction. Additional papers detailing empirical gas transfer parameterizations, 2‐D wave statistics and bubble methods and measurements are in preparation.…”
Section: Resultsmentioning
confidence: 99%
“…Both direct and indirect measurements of sub‐100 nm particle composition at mid‐latitudes have demonstrated the role of secondary organic species in the growth of small particles (Bzdek et al, ; Vaattovaara et al, ). Sub‐Arctic observations of air‐sea fluxes in the Labrador Sea show that the fluxes of isoprene and monoterpenes are significantly lower than that of DMS in autumn; however, events of high biogenic VOC fluxes can have a significant impact on aerosol size distributions (M. J. Kim et al, ).…”
Section: Regional Arctic Processesmentioning
confidence: 99%
“…The EPA O 3 monitor shows a persistent high bias at low O 3 concentrations (< 10 ppbv) relative to the Ox-CIMS. This discrepancy could arise from known interferences from water, mercury, and other species in the 254 nm UV absorbance detection of ozone (Kleindienst et al, 1993).…”
Section: Ozone Field Calibration and Intercomparisonmentioning
confidence: 99%